MAKASSAR CITY GOVERNMENT WEBSITE AS A DIGITAL MEDIA FOR PUBLIC SERVICES - Muhammad Anshar (Jurnal Dakwah Tabligh, 2022)
Public service is the main task of government agencies and public bodies. The principle of good governance provides effective, efficient, transparent, and accountable public services. The Makassar city government has used the website https://makassarkota.go.id/ as digital media for public services. This website provides various information such as logos, names, history, potential, innovations, regional organizations, sub-districts, and news. The website displays the name of the agencies and sub-district in Makassar city with the office address, email, and website. With this facility, the public can obtain information and interact with the Makassar city government electronically. According to Gartner's research, website facilities are in the second stage, namely (1) presence, and (2) interaction. To improve public services, the website needs to be updated, and add transaction facilities (the third stage). Several official websites and sub-district offices that have not been active should be activated to provide services to the residents of Makassar. Keywords Public services, digital media, websites, Makassar City Government